Tinjauan Teologis-Etis dan Politik Wacana Perpanjangan Masa Jabatan Presiden - Kukuh Purwidhianto; Alfred Ruben Gordon Ta’ek (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2022)
The discourse of extending the term of office of the president has become a classic phenomenon that keeps repeating itself. From the old order, the new order to the post-reform era, including during the current administration of President Joko Widodo. This paper describes the polemic of the discourse on extending the term of office of the president and discusses it with thoughts about politics, power, and democratic and theological-ethical government systems. This paper focuses on finding answers to the question, “How did the discourse on extending the presidency during the Joko Widodo administration finally fail in the middle of the road?” From a theological-ethical and political perspective, is it really only because of the better democratic system and the strength of civil society in Indonesia? Or is there another factor that will determine the success and failure of the discourse on extending the presidential term? Through this paper, the author argues that it is the ethical attitude of President Jokowi's leadership that will determine the end of the discourse.